Modeling Bandung Traffic Jam Using Simulation Of Urban Mobility - Yapinus, Pin Panji; P., Ary Setiajadi (Zenit, 2015)
The population density in Bandung City is rapidly increasing. It is also followed by the increasing number of vehicles. Today, people are able to get new vehicles much easier than everbefore. The public services such as trains, buses, and